Revitalisasi Pojok Baca sebagai Upaya Menumbuhkan Kegemaran Membaca di Era Digital - Akib, Tasrif; Aulia Hamid, Arsy; Sari, Nurfirda; Rengganis, Mutiara; Alfiana, Rahmadani; Nurhikmah; A. Nurul Syarfia; Patri, Atriana; Hidayatullah, Rezky (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Advances in digital technology have had a significant impact on the reading behavior of elementary school students. Student reading habits tend to decline due to the predominant use of digital devices for entertainment. Based on this situation, this community service activity was implemented with the aim of increasing students' interest in reading and literacy skills through a reading corner revitalization program at the UPT SDN 73 Bontorita 1 in Bontomangape Village, Galesong District, Takalar Regency, South Sulawesi. The program lasted two months and involved teachers, students, and the school's literacy community. The implementation method used a collaborative participatory approach that included preparation, counseling, training, mentoring, and evaluation. The reading corner revitalization involved designing an attractive reading space, providing printed and digital reading materials, and implementing literacy activities such as shared reading sessions and light book discussions. The results of the activity showed a significant increase in students' reading interest. Based on questionnaires and observations, the frequency of student visits to the reading corner increased by 62% after the revitalization. Seventy percent of students stated that the reading corner became more attractive and comfortable, and 80% of teachers reported increased student participation in reading activities. In addition, a school literacy community was formed that actively manages the reading corner on an ongoing basis. The benefits of this activity noto9oonly create a conducive literacy environment but also strengthen collaboration between teachers, students, and parents in fostering a reading culture. In conclusion, the reading corner revitalization activity successfully integrated physical and digital approaches to increase reading interest in elementary school students. A new aspect that emerged was the active involvement of the entire school community in developing the digital technology-based reading corner as a modern and sustainable literacy learning center.